ANALISIS PENCATATAN DAN PELAPORAN BELANJA MODAL PADA UNIT PELAKSANA TEKNIS DINAS PUSAT PENGEMBANGAN MUTU GURU - Nadiya Nadiya; Eva Susanti; Dedi Juanda (KOLEGIAL, 2018)
This research was conducted at the UPTD Region I Teacher Quality Development Center (PPMG) of the Aceh Education Agency with the aim to find out how the system and procedures, recognition, recording and reporting of capital expenditures at the UPTD Region I Teacher Quality Development Center (PPMG) of the Aceh Education Agency. In analyzing the data this research was conducted with descriptive qualitative methods. The results of the study show that Recording and Reporting on Capital Expenditures at the UPTD Region I Teacher Quality Development Center (PPMG) Aceh Education Agency has implemented Government Regulation No. 71 of 2010 concerning Government Accounting Standards and Minister of Home Affairs Regulation No.64 of 2013 concerning Financial Management Guidelines Country / Region. The expenditure reporting carried out by the UPTD Region I Teacher Quality Development Center (PPMG) of the Aceh Education Agency has implemented PP No. 71 of 2010 concerning accrual-based recordings, which can be seen from the recording of expenditure accounts consisting of operating expenditures covering personnel expenditure and goods and services expenditure and capital expenditure which includes expenditure on equipment and machinery and expenditure on other fixed assets.